(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This is the first in a series of four policy guides developed to support policymakers and practitioners in Asia and the Pacific in their efforts to strengthen social protection. This first guide explains the basic principles of why social protection is needed. The second guide explains the critical steps in designing a social protection scheme; the third focuses on the effective implementation of tax-financed social protection; and the fourth guide discusses options for financing social protection.